Effectiveness, Tolerability and Safety of a Compound Based on D-chiro-inositol + Myo-inositol, Melatonin, Folic Acid, and Vitamin D in Patients with Menstrual Cycle Disorders - Silvia P. González; María del Mar Rubio; Helena Losa (Clinical and Experimental Obstetrics & Gynecology)
Background: Menstrual cycle disorders represent a prevalent cause for gynecological consultations. These disorders often encompass ovulatory dysfunction, accompanied by analytical and clinical anomalies linked to hyperandrogenism, collectively defining polycystic ovary syndrome (PCOS). However, a considerable subset of patients suffering from menstrual cycle disorders fails to meet the diagnostic criteria for any recognized PCOS phenotypes, leading to substantial debate in the field. This study aims to assess the impact of a commercially available combination of inositols, melatonin, folic acid, and vitamin D in patients experiencing menstrual disorders, characterized by oligo-anovulation (amenorrhea and abnormally long cycles), irrespective of their actual compliance with PCOS criteria. Methods: An observational, prospective, non-randomized study was devised to assess cycle regularity, satisfaction levels, and analytical alterations following the administration of the combination of inositols, melatonin, folic acid, and vitamin D (at baseline and at 6 months). Statistical analysis was executed using SPSS (version 22.0). Results: The assessed treatment demonstrated an enhancement in the regularity of menstrual cycles, accompanied by notable reductions in androstenedione and dehydroepiandrosterone (DHEA) levels, as well as basal insulin and the homeostatic model assessment for insulin resistance (HOMA), despite their initial values falling within the normal range. Furthermore, there was a substantial elevation in the serum levels of vitamin D (p < 0.05). Following 6 months of treatment, a high degree of patient satisfaction was observed, with no documented adverse effects within the selected sample. Conclusions: The combination of inositols, melatonin, folic acid, and vitamin D exhibits potential as an efficacious approach for managing menstrual disorders while maintaining a commendable safety profile. Additional investigations into the long-term efficacy and safety of this formulation are warranted, although initial results hold promise.